Hedging of Contracts, Anticipated Positions, and Tender Offers : A Study of Corporate Foreign Exchange Rate Risk And/or Price Risk - Lagerstam, Catharina (Stockholm School of Economics, Economic Research Institute, 1990)
A company is susceptible to the risk incurred by stochastic prices, in the domestic currency unit. the random characteristic steps from a stochastic domestic price or from a stochastic foreign exchange rate possibly combined with a locally stochastic price.